The Parliament’s public relations in terms of political journalism - Vaišnys, Andrius (Žurnalistikos tyrimai, 2015)
While sitting at a place designated for guests in a representative hall of the Lithuanian parliament, the Italian President was smiling at the Speaker of Seimas who was sitting right in front of him and quietly waited until the three minutes dedicated to photojournalists and television cameramen under the protocol were over. When the journalists left, his wide smile vanished, and the President confided to the Speaker of the Seimas that he ‘also’ did not like and even hated journalists but had no other choice than get used to them and be nice because they also ‘were an authority’. He agreed for his words to be translated into Lithuanian and pointed out: “A very powerful authority, unfortunately”. This situation from the end of the 20th century is in no way an exception in terms of the relationship between the media and government even if used in this article as a case example, because the author will present some more of such examples illustrating the issues of public relations (PR) of the parliament in respect of the media. It is just that this scene is quite typical. Even the description of the media as an authority that was voiced that morning was old news since it was publicly announced as in the early as 16th century in the House of Commons of the United Kingdom when observers sitting in the press gallery were called the “fourth estate”. These words of the president, who had a long experience of parliamentary work, reflect the issue of relationship between the government and the media: politicians are constantly striving to make an influence by means of the media while the media, if it is not under the governmental control, naturally distrust politicians, their messages and alleged friendliness to journalists. The journalism, nevertheless, has been recognised as the most effective means of information since the 19th century after the periodic media systems have developed, since it has been able to reach crowds, audiences, public and is still the most effective way to satisfy the need for information about the events and personae of interest to society and therefore is of a permanent interest to political and judicial authorities. That’s why the factor of the media is so important – probably the most important in systemic PR applications. That’s why in our times the structures of authority responsible for PR try not only to understand the methods of journalism but also to ‘integrate’ into the process of journalism to become the main source and even to absorb the nature of the journalism, i.e. to become a medium between a politician and the audience. Let us suppose that social networks allow PR specialists to reach at least part of their audience directly, without using a journalist. Maybe a PR specialist needs to become a journalist then, to reincarnate? The author of this article has a goal to discuss the interaction between the media and public relations when seen through the prism of interests of a state institution. We will use the case of the Lithuanian parliament.
Keywords: journalism; the media; parliament; public relations